Student-teacher relationship: Written feedback provision and writing performance - Sulistyo, Teguh; Dewantara, Arie; Widiastuti, Oktavia; Marhaban, Saiful (Englisia Journal, 2024)
Despite several studies on feedback, little is known about the benefits of the student-teacher relationship in providing feedback. This study therefore aimed to investigate the effects of teacher feedback on students' writing performance. The feedback was divided into two formats: Direct Feedback and Indirect Feedback. Students' writing performance in the study refers to the quality of students' writing when composing a descriptive paragraph. In addition, this study also explored the voices of English as a Foreign Language (EFL) students after being treated with different feedback modes under specific circumstances of the student-teacher relationship. The study adopted a mixed methods design, using a test, a semi-structured interview and a questionnaire as instruments to obtain qualitative and quantitative data. The study involved 50 secondary school students who were divided into two groups of 25 students each. The results showed that direct feedback stimulated students' writing performance better than indirect feedback. In addition, the feedback treatments could maximize students' writing performance if a good student-teacher relationship was developed in the classroom. This implies that maintaining a good student-teacher relationship in the EFL classroom is beneficial.